Advances in Laboratory Testing and Modelling of Soils and Shales (ATMSS) - Ferrari, Alessio; Laloui, Lyesse; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this spirit, the ATMSS International Workshop "Advances in Laboratory Testing & Modelling of Soils and Shales" (Villars-sur-Ollon, Switzerland; 18-20 January 2017) has been organized to promote the exchange of ideas, experience and state of the art among major experts active in the field of experimental testing and modelling of soils and shales. The Workshop has been organized under the auspices of the Technical Committees TC-101 "Laboratory Testing", TC-106 "Unsaturated Soils" and TC-308 "Energy Geotechnics" of the International Society of Soil Mechanics and Geotechnical Engineering. This volume contains the invited keynote and feature lectures, as well as the papers that have been presented at the Workshop. The topics of the lectures and papers cover a wide range of theoretical and experimental research, including unsaturated behaviour of soils and shales, multiphysical testing of geomaterials, hydro-mechanical behaviour of shales and stiff clays, the geomechanical behaviour of the Opalinus Clay shale, advanced laboratory testing for site characterization and in-situ applications, and soil - structure interactions.
Keynote Lectures -- Feature Lectures -- Unsaturated behaviour of soils and shales -- Advanced laboratory testing -- Hydro - Mechanical behaviour of shales and stiff clays -- Opalinus Clay shale -- Advanced laboratory testing for site characterization and in - situ application studies -- Soil - structure interactions -- Constitutive and numerical modelling of soils and shales.
Keywords: Engineering geology; Geotechnical engineering; Soil science; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Soil Science